2011
DOI: 10.1111/j.1601-0825.2011.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of oral human papillomavirus infection in Fanconi’s anemia patients

Abstract: Patients without oral malignant lesions submitted to HSCT, have high prevalence of oral HPV. HPV screening and close follow up should be considered in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 31 publications
4
29
1
2
Order By: Relevance
“…15,20,23 In the present study there was a significant increase in NA and CA and a decrease in the NA/CA ratio of epithelial cells for the FA group when compared to the C group. The increase in the NA and CA could be associated with chronic anaemia caused by medullar aplasia.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…15,20,23 In the present study there was a significant increase in NA and CA and a decrease in the NA/CA ratio of epithelial cells for the FA group when compared to the C group. The increase in the NA and CA could be associated with chronic anaemia caused by medullar aplasia.…”
Section: Discussionsupporting
confidence: 46%
“…FA is a rare disorder resulting from autosomal or rarely X-linked recessive inheritance of mutations in 20 Manifestations of FA appear in the first decade of life and include various malformations such as short stature, abnormality of the thumbs, microcephaly, café au lait hypopigmented spots, renal malformation, and growth retardation. 21 Patients with FA that underwent haematopoietic cell transplantation have an increased susceptibility to the development of squamous cell carcinomas (SCC) of the head and neck compared to FA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that HPV-immortalized FA keratinocytes form hyperplastic epithelium in an organotypic raft culture system compared to complemented cells (36,53). Furthermore, several studies have implicated FA in the increased incidence and aggressiveness of HPV-induced mouse models of cancer (54)(55)(56), and there is controversial evidence that HPV plays a role in the increased incidence of head, neck, and anogenital tumors in FA patients (57)(58)(59)(60). The effects of E6 and E7 on somatic reprogramming were characterized in a previous study, which found that both E6 and E7, alone and in combination, promoted reprogramming by preventing senescence (9).…”
Section: Discussionmentioning
confidence: 99%
“…Pode haver pigmentação da mucosa jugal, língua e palato, atrofia das papilas linguais, redução do fluxo salivar. As alterações radiográficas mais frequentes são microdontia generalizada, ausência de dentes por extrações e agenesias, transposições e supranumerários (ACIKGOZ et al, 2005;DE ARAUJO et al, 2007;TEKCICEK et al, 2007;DE ARAUJO et al, 2011;SHETTY et al, 2011 (STOOPLER et al, 2007;ISLAM et al, 2011). Na literatura investigada, as alterações estomatológicas mais frequentes nos pacientes em preparo para TCTH foram gengivite, acúmulo de biofilme, cálculo dentário, periodontite com bolsas profundas e perda significativa de osso alveolar, alto índice de cárie, redução de fluxo salivar, restaurações com infiltrações necessitando de retratamento, lesões periapicais, raízes residuais, dentes parcialmente irrompidos, mucosite, dor relacionada à articulação têmporo-mandibular, infecções oportunistas por fungos e vírus, infiltrado leucêmico gengival, petéquias, equimoses, língua saburrosa, úlceras traumáticas infectadas, erosão dental, hiperplasia ou hipertrofia gengival, alterações oclusais e na formação dos dentes após quimioterapia na infância (LUCAS et al, 1998;GRABER et al, 2001;MELKOS et al, 2003;VAUGHAN et al, 2005b;YAMAGATA et al, 2006;BRENNAN et al, 2008;DA SILVA SANTOS et al, 2008;DUREY et al, 2009;BOER et al, 2010;HONG et al, 2010;LAAKSONEN et al, 2011;PALMASON et al, 2011;GURGAN et al, 2012;HERNANDEZ-FERNANDEZ et al, 2012).…”
Section: Doenças Onco-hematológicasunclassified